PENDAMPINGAN BELAJAR BANGUN GEOMETRI DENGAN PERANGKAT MAR (MATHEMATIC AUGMENTED REALITY) - Rachmawati Rachmawati; Asri Putri Anugraini (JPM PAMBUDI, 2022)
MAR (Mathematic Augmented Reality) is a learning tool that includes syllabus, lesson plans and student worksheets accompanied by AR (Augmented Reality)-based media. MAR (Mathematics Augmented Reality) is arranged systematically with the aim of exploring the level of student cognition assisted by augmented reality media, containing a series of learning activities, learning objectives have been formulated clearly and specifically with the help of augmented reality-based teaching aids. The geometric shapes presented in this activity are cubes and blocks. This community service activity was carried out at the Bulan Terang Utama Housing Complex, RT 15 RW 16 and was attended by the children of grades V and VI of elementary school.